Kompetensi Spiritualitas Mahasiswa - Novitasari, Yuni (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
This study aims to present spirituality student competency profiles, which can provide a view of cultural competence on the part of students or the spirituality of the people of Indonesia. The method used is survey. Subjects consisted of 50 students on the course for guidance and counseling. Most categories of student spirituality competency is moderate, with highs in the affective aspects, aspects of cognitive and psychomotor lowest at. Therefore, the development of spirituality on student competence becomes important. Especially the development of the cognitive and psychomotor aspects. Competence spirituality is a potential in human beings that can evolve positively. As the results of research and studies mention that spirituality has contributed to mental health, positive moral behavior, professionalism, physical health, as well as character development. Character development is part of a very important educational mission. Moreover, the students as the next generation of nation-building, it is necessary formation of strong character. Belief in God and positive moral behavior is one of the main characters to be achieved in the national education goals. Spirituality can be a major potential in the development of the character.